2009
DOI: 10.1007/s00216-009-2693-0
|View full text |Cite
|
Sign up to set email alerts
|

The spatially resolved characterisation of Egyptian blue, Han blue and Han purple by photo-induced luminescence digital imaging

Abstract: The photo-induced luminescence properties of Egyptian blue, Han blue and Han purple were investigated by means of near-infrared digital imaging. These pigments emit infrared radiation when excited in the visible range. The emission can be recorded by means of a modified commercial digital camera equipped with suitable glass filters. A variety of visible light sources were investigated to test their ability to excite luminescence in the pigments. Light-emitting diodes, which do not emit stray infrared radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(88 citation statements)
references
References 7 publications
1
83
0
4
Order By: Relevance
“…1), in good agreement with the spectral data reported by others from pigments from the same supplier [7,19]. The emission lifetime measured in our commercial pigment is in agreement with Borozov et al [19] but differs with respect to that reported for the synthetic mineral calculated using single photon counting and 637 nm excitation (τ = 107 μs [6]).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…1), in good agreement with the spectral data reported by others from pigments from the same supplier [7,19]. The emission lifetime measured in our commercial pigment is in agreement with Borozov et al [19] but differs with respect to that reported for the synthetic mineral calculated using single photon counting and 637 nm excitation (τ = 107 μs [6]).…”
Section: Resultssupporting
confidence: 92%
“…Whereas ultraviolet (UV) light sources based on Mercury lamps require filtering of spurious radiation emitted in the visible to render them useful for imaging and photography, innovative uses of Xenon-flashes and digital photography have demonstrated the peculiar and noteworthy infrared emissions from Egyptian blue on paintings and painted objects from the British Museum and, more recently, on Fayoum Portraits [7][8][9]. Many other examples of digital imaging of Egyptian blue from objects have been documented.…”
Section: Introductionmentioning
confidence: 99%
“…Webb (2017) used a modified camera for reflected IR imaging of three-dimensional objects investigating the potential integration of IR and 3D imaging for object documentation. In addition to reflected IR imaging, modified cameras are being used for visible-induced IR luminescence imaging to detect Egyptian blue (Kakoulli et al, 2017;Verri, 2009) and visible-induced visible luminescence to detect madder lake (Kakoulli et al, 2017). Falco (2009) and Verhoeven et al (2009) presented cultural heritage and archaeological applications for modified digital cameras and their studies included characterisation and assessment of the modified cameras.…”
Section: Modified Camerasmentioning
confidence: 99%
“…El color azul se obtenía en época romana con un pigmento sintético muy particular, cuya invención se produjo en el Antiguo Egipto: el Egyptian Blue. En fechas muy recientes G. Verri (2009), conservador del British Museum, ha desarrollado una técnica fotográ-fica que permite detectar, con relativa facilidad y sin análisis químicos, vestigios de tal pigmento en piezas arqueológicas, denominada Visible Induced Luminescence (VIL) digital imaging (Verri 2009). La técnica se basa en la propiedad que presenta el tetrasilicato cálcico de cobre, compuesto fundamental del pigmento, de absorber la radiación lumínica visible y re-emitir Este grupo fue estudiado por A. Ventura, quien lo vinculó a dicho templo (Ventura 2007).…”
Section: Introductionunclassified